PENGARUH WORK-LIFE BALANCE DAN COACHING TERHADAP KINERJA KARYAWAN MELALUI EFIKASI DIRI SEBAGAI VARIABEL MEDIASI (Studi Kasus pada Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Cabang Palangka Raya Kalimantan Tengah) - Sharfina Fauziyah Wahyudi (2022)
The purpose of this study is to determine and prove the influence of work-life balance on employee performance, to determine and prove the influence of coaching on employee performance, to determine and prove the influence of work- life balance on employee performance mediated by self-efficacy, to determine and prove the influence of coaching on employee performance mediated by self- efficacy, and to determine and prove the influence of self-efficacy on employee performance. This study uses quantitative approach with a sample size of 31 employees of BPJS Ketenagakerjaan Cabang Palangka Raya using saturated sampling method. The Structural Equation Model (SEM) based on Partial Least Square (PLS) was adopted in this study. This study used SmartPLS 3.0 as a tool for data analyzing. The results of this study found that (1) work-life balance has no effect and is not significant on employee performance, (2) coaching has a positive and significant effect on employee performance, (3) work-life balance has a positive and significant effect on employee performance mediated by self-efficacy, (4) coaching has a positive and significant effect on employee performance mediated by self-efficacy, and (5) self-efficacy has a positive and significant effect on employee performance.